Electric vehicle charging infrastructures in the Greater Bay Area of China: Progress, challenges and efforts - Lau, Yui-yip; Andrew Wu, Yang; Wing Yan, Mak (Frontiers in Future Transportation, 2022)
The electric vehicle (EV) has proven to be a workable solution to minimizing environmental pollution. The EV has generally received substantial attention from both individual customers and corporate users. The EV has transformed remarkably and in recent years emerged as the most quickly developing section of the automobile industry. China has proven to be an outstanding country in enhancing the manufacture and marketing of EVs. Nevertheless, green environment, charging infrastructure and technology are the three main challenges leading to slowing down the penetration progress of EVs into the Greater Bay Area (GBA) of China. This study aims to report the existing development of the EV industry in China. Then, it elaborates on national policies to facilitate the enlargement of charging infrastructures, explains how to stimulate the development of charging infrastructure at the national level, discusses the implementation dilemma at the provincial and city levels, and highlights the challenges and policy gaps. Finally, it addresses some issues, challenges, progress and implications for improving the EV penetration in the GBA in the forthcoming years.